2005
DOI: 10.1093/ajcn/81.6.1275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adipose tissue gene expression with energy-restricted diets in obese women1–4,

Abstract: Macronutrients have a secondary role in changes in adipocyte gene expression after energy-restricted diets. The most striking alteration after energy restriction is a coordinated reduction in the expression of genes regulating the production of polyunsaturated fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 32 publications
8
106
3
3
Order By: Relevance
“…Several recent studies have examined how nutrition affects gene expression in the context of obesity and metabolic syndrome (40,41). These investigations (the FUNGENUT study) profiled gene expression in subcutaneous adipose tissue and found downregulation of IGF pathway genes and genes related to fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined how nutrition affects gene expression in the context of obesity and metabolic syndrome (40,41). These investigations (the FUNGENUT study) profiled gene expression in subcutaneous adipose tissue and found downregulation of IGF pathway genes and genes related to fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…One such identified obesity candidate gene is CIDEA. 4,5 Of course, there are limits to the usefulness of the microarray approach for identifying adipose genes of importance for obesity. For genes differentially expressed between case and control cohorts, we cannot differentiate between what is primary cause and what is secondary association; one consistent finding is upregulation of inflammatory genes in adipose tissue of obese humans, which intuitively is of greater importance for the metabolic complications of obesity than for obesity per se.…”
Section: Modern Approaches To Discover Adipose Tissue Genes Contributmentioning
confidence: 99%
“…[19][20][21][22][23] A few studies have applied microarray technologies to study gene expression in AT of massively obese subjects either in comparison to lean subjects cross-sectionally 24,25 or after short-term weight reduction. 26,27 These studies have demonstrated downregulation in the expression of genes involved in inflammation and desaturation of fatty acids. 26,27 In the present work, we studied the effect of long-term weight reduction on gene expression in AT of overweight or obese individuals with impaired fasting glycemia or impaired glucose tolerance and other features of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 These studies have demonstrated downregulation in the expression of genes involved in inflammation and desaturation of fatty acids. 26,27 In the present work, we studied the effect of long-term weight reduction on gene expression in AT of overweight or obese individuals with impaired fasting glycemia or impaired glucose tolerance and other features of the metabolic syndrome. We aimed to examine the effect of the long-term moderate weight reduction on gene expression in AT and to identify genes and gene clusters responsive to treatment and thereby likely contributing to the development of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%